5-minute snuggle stories. (Disney Press, 2013)
"12 enchanting adventures, featuring favorite Disney and Disney 2EPixar characters from "Monsters, Inc., The Lion King, Tangled, " and more, each taking only five minutes to read."--Provided by publisher.